App inventor for Android build your own apps-- no experience required! - Tyler, Jason, 1976- (Wiley, 2011)
"Google App Inventor for Android is the complete guide to App Inventor for Android, Google's new visual language for building mobile apps. With App Inventor, you program by piecing together blocks that represent the phone's functionality. Because it's like putting together a puzzle, even non-technical people can use App Inventor to create mobile apps. With App Inventor you don't need to write a single line of programming code, and can still create apps that take advantage of all of an Android smart phone's features including the accelerometer, GPS, messaging, contacts, the web and more. This book provides you with a series of fully worked out apps that you can create, download and use on your Android phone. Best of all, the apps come with complete "source blocks", fully explained in easy to understand terms, which you can customize for your own use or use as a model for building the next "killer app". The sample apps are accompanied by a section on App Inventor Designs Patterns that serves as an invaluable reference and explains computer science concepts in simple terms. Google App Inventor for Android is the perfect companion for your app exploration, and will have you creating your own Android apps in no time"--